INTERFERENSI BAHASA PAKPAK DIALEK BOANG PADA PENGGUNAAN BAHASA INDONESIA - Azwir Kartono; Jusrin Efendi Pohan; Esra Perangin-angin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Language interference often occurs in bilingual or multilingual communities that influence each other. Language becomes a medium of communication to achieve the conventions of a language community. Language is not merely an instrument for conveying information, but rather a system that contains certain meanings or messages. Language interference is not only negative, but also has positive nuances for the language-using community. It can facilitate interaction and communication between the sender and the recipient of the message. Viewed from the negative side, language interference makes the language community dislike the target language. This makes the Pakpak language community of the Boang Dialect in using Indonesian, more towards the lack of knowledge or understanding of Indonesian, resulting in a negative impact on the community of Indonesian. This type of research is a qualitative descriptive study with a sociolinguistic approach. This research will reveal an in-depth and clear picture of the occurrence of language errors that result in interference at the phonological, morphological, syntactic, and semantic levels in Dah Village, Rundeng District, Subulussalam City. This study shows that the interference of the Pakpak Boang dialect on the use of Indonesian in Dah Village, Subulussalam City, has a negative impact, reviewed from the aspects of the factors causing the interference, identifying the impacts caused by the interference, and solutions. This is closely related to the Pakpak Boang community's ability to speak good and correct Indonesian.